Interaction between parasite and vector for Malaria disease transmission-a review on Malaria (Progressive Agriculture, 2016)
The parasite, Plasmodium needs an insect vector (mosquito) and a vertebrate host (human) to successful malaria transmission. The parasite use the vertebrate hosts for their asexual reproduction and insect host for sexual multiplication. In order to know the mechanism of disease transmission, knowledge about the possible interactions causes by the three components, vector, parasite and host is important. The mosquito feeding behaviour greatly contributes in the rate of malaria transmission. To assist the rate of transmission of malaria, the parasite, Plasmodium completes a complex developmental stage in the mosquito. In the mosquito the parasite, passes complex developmental stages and ensuing changes into three important forms of their life cycle: ookinete, oocyst and sporozoites. This review study concludes that, the interactions among vector, parasite and host in terms of reproductive behaviour and blood-feeding behaviour helps in transmitting malaria to the vertebrate hosts mainly, human being.Progressive Agriculture 27 (2): 168-174, 2016